2016
DOI: 10.1371/journal.pone.0168036
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Niche Activity of Ex-Vivo Expanded MSCs as Factor for Variable Outcomes in Hematopoietic Recovery

Abstract: Ex-vivo expanded mesenchymal stromal cells (MSCs) are increasingly used for paracrine support of hematopoietic stem cell (HSC) regeneration, but inconsistent outcomes have hindered ongoing clinical trials. Here, we show that significant heterogeneity in the niche activity of MSCs is created during their culture in various serum-supplemented media. The MSCs cultured under stimulatory or non-stimulatory culture conditions exhibited differences in colony forming unit-fibroblast contents, expression levels of cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…We also found that mice treated with inhibitors of CXCL-12 and Jagged-1 (AMD3100 and DAPT, respectively) caused significant decrease of hematopoietic progenitor pool in BM and knock down of Jagged-1 decreased in-vitro self-renewal of the progenitor cells (Fig. 2E–G), in consistence to previous observations 12,41,42 . Taken together, these results show that the neonatal BM microenvironment is characterized by higher proportions of primitive MSC subsets with increased expression of niche cross-talk molecules that can support higher self-renewal of HSCs than in adult BM.
Figure 2Difference in the expression levels of niche cross-talk molecules in mesenchymal stroma of neonate and adult BM.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that mice treated with inhibitors of CXCL-12 and Jagged-1 (AMD3100 and DAPT, respectively) caused significant decrease of hematopoietic progenitor pool in BM and knock down of Jagged-1 decreased in-vitro self-renewal of the progenitor cells (Fig. 2E–G), in consistence to previous observations 12,41,42 . Taken together, these results show that the neonatal BM microenvironment is characterized by higher proportions of primitive MSC subsets with increased expression of niche cross-talk molecules that can support higher self-renewal of HSCs than in adult BM.
Figure 2Difference in the expression levels of niche cross-talk molecules in mesenchymal stroma of neonate and adult BM.
…”
Section: Resultssupporting
confidence: 90%
“…Next, to compare the microenvironmental function of mesenchymal cells in neonatal and adult BM, we compared expression of extracellular signaling molecules, Jagged-1 and CXCL-12, in BM mesenchymal cell population, the two molecules in BM niche that serve as cross-talk signals to regulate HSC self-renewal 12,41 . We found that MSCs in neonatal BM expressed significantly higher levels of CXCL-12 and Jagged-1, compared to MSCs from adult BM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the BM microenvironment should undergo dynamic changes in niche activity to accommodate the alternating needs for hematopoietic activity. Consistent with this view, we have shown that the mesenchymal cells can undergo reversible changes during cell culture, exhibiting distinct niche activities [29], and that these niche activities are regulated by changes in signals from canonical Wnt or notch ligands, for example [17,30], as well as by the molecular gradient for the epithelial-mesenchymal transition (EMT), as observed in a model for 3-D mesenspheres [31]. However, the dynamic changes in the BM niche in response to varying physiological demands, which reveal how the regenerative process for maintaining body homeostasis is controlled, remains largely unknown.…”
Section: Introductionsupporting
confidence: 83%
“…Murine hematopoietic progenitor were enriched by pretreatment with 5-Fluorouracil (150 mg/kg; 5-FU, Sigma-Aldrich, St. Louis, MO) 4 days before BM harvest, or by immunomagnetic separation of progenitors using Mouse hematopoietic progenitor cell enrichment kit (StemSep, STEMCELL Technologies, Vancouver, BC). MSCs from murine BM were obtained by serial culture for adherent cells until all adherent cells become CD45 negative as described [29]. Mouse endothelial cells (bEnd.3, ATCC CRL-2299) were cultured in DMEM supplemented with 10% fetal bovine serum (FBS).…”
Section: Cellsmentioning
confidence: 99%
“…Similarly, studies have shown that MSCs expanded under conventional in vitro culture by plastic adherence undergo functional and phenotypic changes during the passage of cultures, creating features that are distinct from those of in vivo isolated MSCs 9 . In addition, our recent study showed that the cellular characteristics of MSCs to support stem cells exhibit dynamic changes according to the pathological changes in bone marrow microenvironment or intensity of the canonical Wnt signaling pathways 10 , 11 and can exhibit reversible changes in niche activity by switching of culture conditions 12 , thus pointing possible heterogeneity in the supporting function of MSCs with respect to the culture conditions.…”
Section: Introductionmentioning
confidence: 99%